STRUKTUR DENDANG LELA AMPALU DALAM RABAB PASISIA DI DESA AMPALU KECAMATAN SUTERA KABUPATEN PESISIR SELATAN - Khairullah, Khairullah; Marzam, Marzam (SENDRATASIK UNP, 2019)
Abstract The purpose of this research was to describe the dendang lela ampalu in the presentation structure of Rabab Pasisia in Ampalu Village, Kecamatan Sutera, Pesisir Selatan Regency. This type of research was a qualitative study using descriptive methods. The main instrument in this study was the researcher self and assisted with supporting instruments such as stationery and cameras. Techniques of data collection were observation, literature study, interviews and documentation. The steps for analyzing data were collecting data, clarifying data and making conclusions.The results showed that Dendang Lela Ampalu was included in the structure of the presentation of dendang in a Rabab Pasisia show. However, Dendang Lela Ampalu does not stand alone but Dendang Lela Ampalu is also a part of the Dendang. Dendang Lela Ampalu is conveying the message of suffering experienced by a household. In the past, Dendang Lela Ampalu was only sung by mothers who were initially without any instruments. But at this time Dendang Lela Ampalu has been accompanied by the instrument of Rabab Pasisia and displayed in the performing arts of Rabab Pasisia Keywords: Structure, Dendang Lela Ampalu, Rabab Pasisia